The Implementation of Sharia Principles in Stock Trading: A Comparative Analysis of Conventional and Sharia-Compliant Stock Markets - Putri, Riska Fitri Anggina; Azizah, Iffah; Awani, Renada; J, Jaenudin; Herdiana, Dian (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the fundamental differences between transaction mechanisms in the conventional stock market and the sharia-compliant stock market, as well as to examine the application of sharia principles—such as the prohibitions of riba, gharar, and maysir—in sharia stock trading. In addition, this research evaluates the effectiveness of regulations and supervisory systems in enforcing sharia principles within the Indonesian capital market. The method used is library research by reviewing various sources including scientific journals, books, and official documents from the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The findings show that the sharia stock market has stricter and more transparent mechanisms compared to the conventional market because all instruments and commitments must undergo a sharia screening process to ensure compliance with Islamic principles. The prohibitions of riba, gharar, and maysir are enforced through the avoidance of interest-based transactions, speculative activities, and excessive uncertainty. Regulations issued by OJK and DSN-MUI have played a crucial role in maintaining the integrity of the sharia market, although stronger supervisory systems and improved investor literacy are still needed. Overall, Indonesia’s sharia stock market demonstrates significant potential as an ethical investment alternative grounded in transparency and economic sustainability.